Novel Lauh Mahfuz: Agama dan Harmonisasi Keberagamaan - Arif Hidayat (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Humans are diverse, full of differences, unique, and have a mindset of each, there are always hidden sides in it, dark corners that must be read carefully and carefully to lead to the true meaning because they all have the possibility to be interpreted. and interesting to be appreciated. Likewise, the novel Lauh Mahfuz by Nugroho Suksmanto, which is full of meaningful messages related to understanding religion, overcoming differences and harmonizing diversity. It needs to be known and understood that to understand it is not only built through the arrangement of events, but can also be raised through the background of certain social and cultural systems. In the novel Lauh Mahfuz, the character becomes a